Developing reading skills : advanced - Markstein, Linda. 4 0 16; Hirasawa, Louise; 5 (Rowley, MA : Newbury House, 1983)
A collection of texts emphasizing guided reading practice and the development of reading speed, for those who want to strengthen their reading skills for academic, personal, or career purposes.
Keywords: 2 -- 0; 6; Textbooks for foreign speakers.;Textbooks for foreign speakers. -- English language;Readers;English language;Readers. -- 1950-20; 20; 2